2014
DOI: 10.1111/1365-2656.12173
|View full text |Cite
|
Sign up to set email alerts
|

Heterochrony in a complex world: disentangling environmental processes of facultative paedomorphosis in an amphibian

Abstract: Summary1. Heterochrony, the change in the rate or timing of development between ancestors and their descendants, plays a major role in evolution. When heterochrony produces polymorphisms, it offers the possibility to test hypotheses that could explain its success across environments. Amphibians are particularly suitable to exploring these questions because they express complex life cycles (i.e. metamorphosis) that have been disrupted by heterochronic processes (paedomorphosis: retention of larval traits in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 60 publications
4
53
0
Order By: Relevance
“…Unfortunately, detection probability cannot be integrated into kernel analysis. Nevertheless, previous analyses showed that detection probability with the survey methods is very high in the study area, therefore, analyses not taking into account detection probability yield results that are nearly identical to analyses integrating detection probability (Denoe¨l and Ficetola 2014). In order to depict the effect of the two kernel approaches (without/with barrier) and of the KDE values (i.e., isopleths of different percentages, from 10% to 95%) on the surface of the utilization distribution, we used linear mixed models.…”
Section: Statistical Analysesmentioning
confidence: 67%
See 2 more Smart Citations
“…Unfortunately, detection probability cannot be integrated into kernel analysis. Nevertheless, previous analyses showed that detection probability with the survey methods is very high in the study area, therefore, analyses not taking into account detection probability yield results that are nearly identical to analyses integrating detection probability (Denoe¨l and Ficetola 2014). In order to depict the effect of the two kernel approaches (without/with barrier) and of the KDE values (i.e., isopleths of different percentages, from 10% to 95%) on the surface of the utilization distribution, we used linear mixed models.…”
Section: Statistical Analysesmentioning
confidence: 67%
“…The absence of paedomorphic individuals in these habitats is caused by a variety of factors (Denoe¨l and Ficetola 2014). For instance, shallow ponds could dry up and thus host metamorphic individuals only.…”
Section: Conservation Areas For Rare Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 for a map of the area). They were classed in three categories (hereafter pond type): ten ponds (hereafter control ponds) have never been reported to have contained fish (Gabrion et al 1977;Denoël and Ficetola 2014); ten ponds (hereafter extirpation ponds) had fish that were extirpated by conservation management (i.e., removal, n = 4) or natural disappearance (n = 6) between 2000 and 2006; and ten ponds (hereafter fish ponds) had fish present during the 2014 survey (Supplementary Table 1). Previous visits to the fish ponds showed that they also contained fish in the period .…”
Section: Study Sitesmentioning
confidence: 99%
“…The presence of fish in extirpation ponds was also determined by our own previous field observations for eight ponds and by local reports for two ponds (Rondeau et al 2000) (Supplementary Table 1). All of the studied ponds were selected to have adequate features (except fish presence in fish ponds) to sustain newt populations and paedomorphs, following our previous results on the ecology of palmate newts in Larzac (Denoël and Lehmann 2006;Denoël and Ficetola 2014). This means that temporary and recently built ponds were not included in this study.…”
Section: Study Sitesmentioning
confidence: 99%